Gorgias/Gorgias: The Sicilian Orator and the Platonic Dialogue with new translations of the Helen, Palamedes, and On Not Being - Montgomery Ewegen, S. (Parnassos Press - Fonte Aretusa, 2022)
Gorgias of Leontinoi in Sicily is widely considered to be the most prominent and important of the sophists. He traveled to Athens in 427 BCE-about the time Plato was born-where he earned both the ire of philosophers and the obols of young men keen on learning the powerful art of logos. As the dialogue named for him shows, Gorgias is representative for Plato of rhetoric and sophistry and all the ways in which they stray from, or even threaten, the philosophical attainment of truth, thereby imperiling the well-being of the polis. Although some of Gorgias's work survives-and is included here in new translations-none of it is as widely studied as Plato's Gorgias. For this and other reasons, there has been a scholarly tendency to treat rhetoric and Gorgias himself as opposed, or even antithetical to, philosophy. As the articles in this volume make clear, however, there is much that is philosophical in Gorgias's work, just as there is much that is rhetorical in the method of Plato's Socrates. In fact, there is great nuance to Plato's treatment of Gorgias's rhetorical abilities, and Gorgias himself can be understood as a subtle and sophisticated (in the positive sense) philosopher. In short, the papers collected here show that the relationship between Plato and Gorgias-and, more generally, between philosophy and rhetoric-is much more complicated, and potentially more mutually beneficial, than is traditionally recognized.Edited by S. Montgomery Ewegen and Coleen P. Zoller, the volume contains new translations of Gorgias's Helen, Palamedes, and On Not Being, introduced by Jurgen R. Gatt. In addition to Ewegen and Zoller, essays have been contributed by Livio Rossetti, François Renaud, R.J. Barnes, Mauro Serra, Stamatia Dova, Erminia Di Iulio, Enrico Piergiacomi, Edward Schiappa, Yosef Z. Liebersohn, Robert Metcalf, and Sonja Tanner.